Narrow absorption lines complex I: one form of broad absorption line. Issue 3 (17th November 2017) - Lu, Wei-Jian; Lin, Ying-Ru
Abstract: We discover that some of the broad absorption lines (BALs) are actually a complex of narrow absorption lines (NALs). As a pilot study of this type of BAL, we show this discovery through a typical example in this paper. Utilizing the two-epoch observations of J002710.06-094435.3 (hereafter J0027-0944) from the Sloan Digital Sky Survey (SDSS), we find that each of the C iv and Si iv BAL troughs contains at least four NAL doublets. By resolving the Si iv BAL into multiple NALs, we present the following main results and conclusions. First, all these NALs show coordinated variations between the two-epoch SDSS observations, suggesting that they all originate in the quasar outflow, and that their variations are due to global changes in the ionization condition of the absorbing gas. Secondly, a BAL consisting of a number of NAL components indicates that this type of BAL is basically the same as the intrinsic NAL, which tends to support the inclination model rather than the evolution model. Thirdly, although both the C iv and Si iv BALs originate from the same clumpy substructures of the outflow, they show different profile shapes: multiple absorption troughs for the Si iv BAL in a wider velocity range, while P-Cygni for the C iv BAL in a narrower velocity range. This can be interpreted by the substantial differences in fine structure and oscillator strength between the Si iv λλ1393, 1402 and C iv λλ1548, 1551 doublets. Based on the above conclusions, we consider that the decomposition of a BAL into NALs can serve as a way to resolve the clumpy structure for outflows, and it can be used to learn more about characteristics of the clumpy structure and to test the outflow model, when utilizing high-resolution spectra and photoionization model.